Tobacco-specific nitrosamine adducts: studies in laboratory animals and humans. - Hecht, S S (1993)
This paper describes quantitation of human hemoglobin and DNA adducts of the carcinogenic tobacco-specific nitrosamines 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N'-nitrosonornicotine (NNN). NNK and NNN are believed to be involved in cancers of the lung, esophagus, oral cavity, and pancreas in people who use tobacco products. The adduct dosimetry method employs GC-MS for quantitation of 4-hydroxy-1-(3-pyridyl)-1-butanone (HPB) released by mild base hydrolysis of hemoglobin or acid hydrolysis of DNA as a biochemical marker of the pyridyloxobutylation metabolic activation pathway. Approximately 22% of smokers (n = 101) had elevated levels of HPB released from hemoglobin (range, 200-1600 fmole/g Hb). Adduct levels in snuff dippers ranged from 200-1800 fmole/g Hb. HPB levels in nonsmokers were generally below the detection limit. Acid hydrolysis of lung and tracheal DNA obtained at autopsy and analysis for released HPB revealed levels ranging up to 50 fmole/mg DNA in smokers; the adduct was not detected in nonsmokers. These findings are consistent with data generated in studies of adduct formation by NNK in rats. The biological significance of the HPB-releasing DNA pyridyloxobutylation pathway was compared to that of the DNA methylation pathway in the A/J mouse. These studies demonstrated that the persistence of O6-methylguanine in lung DNA is critical for tumorigenesis by NNK and that pyridyloxobutylation enhances both persistence of O6-methylguanine and tumorigenesis by acetoxymethylmethylnitrosamine. In the rat, the relative roles of methylation and pyridyloxobutylation in lung tumorigenesis by NNK are not as clearly defined.(ABSTRACT TRUNCATED AT 250 WORDS)